Surveillance of Influenza-Like Illness in France. The Example of the 1995/1996 Epidemic - Carrat, Fabrice; Flahault, Antoine; Boussard, Eric; Farran, Nathalie; Dangoumau, Laure; Valleron, Alain-Jacques (Journal of epidemiology and community health (1979), 1998)
Study objectives-To discover if continuous computerised collection of morbidity data through a medical practice based sentinel network can be used to monitor influenza-like illness (ILI) epidemics. To obtain rough estimates of influenza vaccine effectiveness. Design-Continuous passive surveillance of ILI through a computerised network of voluntary sentinel general practitioners (SGPs) in France (Sentinelle system). Setting-Five hundred SGPs practices. Participants-Since 1984, SGPs updated a database with information on eight communicable diseases including ILI, via videotext terminals. Each ILI case is defined by the association of a sudden fever of 39°C or above, respiratory symptoms, and myalgias. An ILI epidemic is detected when the national weekly incidence rate exceeds a seasonal threshold for two successive weeks. Main results-An ILI epidemic was reported from November 1995 to January 1996. In total, 13 951 individual cases were reported by SGPs during the epidemic period. The size of the epidemic (number of patients consulting a GP) was estimated to be 2 370 000 subjects. Maps of the epidemic showed that all regions have reported a high level ILI activity. The attack rate was the highest in school age children (13.5/100) and decreased as the age rose. Nearly 6% of the reported ILI cases among adults and elderly were vaccinated. The flu vaccine effectiveness against ILI was estimated to be 66% (95% CI 73%, 92%), ranging between 83% (95% CI 73%, 92%) among the subjects aged 15 to 24 years old to 16% (95% CI -12%, 44%) among the subjects aged 75 years or older. Conclusions-The Sentinelle system demonstrated adequate sensitivity and timeliness regarding ILI epidemic. Moreover, results of the monitoring were made available on the internet to increase the dissemination of information. Also, estimates of influenza vaccine effectiveness have been easily obtained. Altogether, they represent key points for the control of crisis situation such as ILI epidemics or pandemics.